Research on the Polishing Process of Wolter-I Type Grazing Incidence Mirrors - Song Ding; Shuhai Yao; Liwei Sun; Fangpu Feng; Dongling Chen (PLoS ONE, 2025)
As the demand for solar X-ray observation devices continues to rise, the Wolter-I type grazing incidence mirror has emerged as a critical component in these instruments, particularly for high-precision imaging. This mirror efficiently focuses X-rays, enabling astronomers to detect fainter celestial signals. It plays a key role in providing essential data for understanding the origin and evolution of the universe. The operating principle of the Wolter-I type grazing incidence mirror is based on grazing incidence reflection. This reflection guides X-rays to a focal point through a specific surface structure, enabling high-resolution imaging. This paper presents the design of a super-precision optical processing system for the Wolter-I type mirror. The system features a coaxial Confocal structure, consisting of a rotating parabolic surface and a rotating hyperbolic surface. It also includes a radial adjustment fixture and an automatic polishing fluid supply device. The paper outlines the imaging principles of the Wolter-I mirror, analyzes the impact of surface shape accuracy on imaging performance, and selects microcrystalline glass as the mirror substrate. Using the custom-designed processing system, the rough-turned workpiece undergoes several steps. After diamond wheel grinding, the workpiece is subjected to 160 hours of rough polishing. It then undergoes 720 hours of fine and super-fine polishing, using cerium oxide polishing fluids with particle sizes of W2, W1, and W0.8, respectively. The final surface shape accuracy of the mirror is characterized by a peak-to-valley (PV) value of 253 nm, a root mean square (RMS) value of 3.5 nm, and a root mean square roughness (Rq) of 4.6 nm. These values meet the requirements for composite extreme ultraviolet-soft X-ray telescopes. Experimental results show that the designed super-precision optical processing system effectively improves surface shape accuracy. It is well-suited for processing the unique internal surfaces of Wolter-I type grazing incidence mirrors. This system enhances the mirror's imaging performance and lays a solid foundation for future high-resolution X-ray astronomical observations. Future research will focus on optimizing the processing techniques further, exploring the impact of different materials on imaging quality, and developing more advanced optical systems to meet emerging observational needs.